Exuberant Behaviour in The Istanbul Housing Market Before and During The Time of The COVID-19 Pandemic: Evidence from The Aggregate and Disaggregate Levels - Gündüz, Lokman; Tekin, Sumeyye Büşra; Özer, Merve; Genç, İsmail H. (Taylor & Francis, 2023)
We study mildly explosive behaviour in house prices in Istanbul at both aggregate and disaggregate levels via GSADF tests. In contrast to previous studies, our results suggest multiple episodes of price exuberance in Istanbul and most districts. Most boroughs synchronically experienced explosive house prices in 2014–2015; and more powerfully during the last episodes of COVID-19. We also show that financial variables, including low mortgage interest rates and high stock prices, increased the probability of explosiveness.
Keywords: Exuberance; GSADF test; House Prices; İstanbul; COVID-19